2011
DOI: 10.5194/tc-5-551-2011
|View full text |Cite
|
Sign up to set email alerts
|

Refined broad-scale sub-glacial morphology of Aurora Subglacial Basin, East Antarctica derived by an ice-dynamics-based interpolation scheme

Abstract: Abstract. Ice thickness data over much of East Antarctica are sparse and irregularly distributed. This poses difficulties for reconstructing the homogeneous coverage needed to properly assess underlying sub-glacial morphology and fundamental geometric constraints on sea level rise. Here we introduce a new physically-based ice thickness interpolation scheme and apply this to existing ice thickness data in the Aurora Subglacial Basin region. The skill and robustness of the new reconstruction is demonstrated by c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…ICECAP used a long-range ski-equipped DC-3T modified for aerogeophysics by the University of Texas, and equipped with ice-penetrating radar, gravimeter, magnetometers and laser altimeters to investigate the geometry (Roberts and others, 2011), long-term history (Young and others, 2011), stratigraphy (Cavitte, 2011) and subglacial hydrology (Wright and others, 2012) The ICECAP geophysical system was installed on the aircraft at the McMurdo seasonal sea-ice runway at the start of each field season. Installation was followed by a calibration flight involving multiple crossovers over flat ice.…”
Section: Field Operationsmentioning
confidence: 99%
“…ICECAP used a long-range ski-equipped DC-3T modified for aerogeophysics by the University of Texas, and equipped with ice-penetrating radar, gravimeter, magnetometers and laser altimeters to investigate the geometry (Roberts and others, 2011), long-term history (Young and others, 2011), stratigraphy (Cavitte, 2011) and subglacial hydrology (Wright and others, 2012) The ICECAP geophysical system was installed on the aircraft at the McMurdo seasonal sea-ice runway at the start of each field season. Installation was followed by a calibration flight involving multiple crossovers over flat ice.…”
Section: Field Operationsmentioning
confidence: 99%
“…Most of the ice sheet that drains through the Totten Glacier is from the Aurora Subglacial Basin and is marine based (i.e. the ice base is grounded below sea level; Roberts et al, 2011) making the region potentially vulnerable to rapid ice sheet collapse. Weertman (1974) showed that ice grounded below sea level is inherently unstable, particularly where the bedrock slopes downwards, away from the ocean, as is the case in the Aurora Subglacial Basin .…”
Section: Introductionmentioning
confidence: 99%
“…Flow-orientation information can be used to refine ice-flux estimates in flux-balance simulations (Wu and Jezek, 2004), especially for Lagrangian-type flux-balance codes (e.g. Testut and others, 2003;Roberts and others, 2011). In addition, flow-direction information is frequently required in determining surface ice-sheet velocities using InSAR techniques, where the flow direction is usually assumed to correspond to the direction of steepest descent of the ice-sheet surface, derived from digital elevation models.…”
Section: Discussionmentioning
confidence: 99%